2019
DOI: 10.3390/jmse7020030
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Dense Shelf Water Cascades along the Rottnest Continental Shelf in Southwest Australia

Abstract: Along the majority of Australian shallow coastal regions, summer evaporation increases the salinity of shallow waters, and subsequently in autumn/winter, the nearshore waters become cooler due to heat loss. This results in the formation of horizontal density gradients with density increasing toward the coast that generates gravity currents known as dense shelf water cascades (DSWCs) flowing offshore along the sea bed. DSWCs play important role in ecological and biogeochemical processes in Australian waters thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The main parameters we used to analyse the LSB system were the wind vectors (10 m above mean sea level) and the surface currents. The same atmospheric and ocean model combination was used by Mahjabin et al [67] to examine dense water transport in the study region.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…The main parameters we used to analyse the LSB system were the wind vectors (10 m above mean sea level) and the surface currents. The same atmospheric and ocean model combination was used by Mahjabin et al [67] to examine dense water transport in the study region.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…These studies were limited to specific locations and did not examine the seasonal variability and its forcing mechanisms. In shallow continental shelf regions, the dynamical balance consists of buoyancy, Coriolis, and friction terms, and hence DSWC moves offshore at an angle to the coastline 23 . This paper used an extensive multi-year ocean glider data set obtained from 8 locations around the Australian continent under a range of incident tide and wind conditions that also enabled us to resolve seasonal variability.…”
Section: Discussionmentioning
confidence: 99%
“…In the relatively narrow shallow continental shelf regions considered in this study, the dynamical balance consists of buoyancy, Coriolis, wind and tidal induced vertical mixing and friction. This results in the DSWC being moved offshore and deflected to the left at some angle to the coastline 23 . Majority of the locations contained relatively uniform bathymetry with a slight offshore gradient.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…The study region is located at 32 • S, close to the critical latitude (30 • S), where the inertial period is 24 h. Because the diurnal sea breeze system also has a ∼ 24 h period, resonance occurs, which generates near-inertial waves (Mihanović et al, 2016;Chen, 2017). Field measurements revealed that near-inertial waves force the thermocline to oscillate at a diurnal timescale with a vertical excursion > 50 m (Mihanović et al, 2016;Chen, 2017). This vertical excursion of the thermocline causes the thermocline to migrate along the continental slope on a diurnal timescale.…”
Section: Discussionmentioning
confidence: 99%